Simple and Practical Real-Time Analysis of Solid-Phase Reactions by Thin-Layer Chromatography - Wu, Chia-Hui; Chen, Chun C.; Lin, Su-Ching; Wang, Cheng-Chung (Synlett, 2018)
Solid-phase synthesis is a practical approach for simplifying the time-consuming and routine purification steps in the preparation of numerous naturally occurring molecules; however, studying such reactions is difficult due to the lack of a convenient monitoring method. By using thin-layer chromatography in conjunction with a photolabile linker on a resin, we developed a convenient and simple method for monitoring solid-phase reactions in real time by thin-layer chromatography. This method provides a user-friendly protocol for examining reaction conditions for solid-state syntheses.
Keywords: solid-phase reactions; real-time analysis; thin-layer chromatography; photolabile linkers; glycosylation; click chemistry